Magnetic resonance imaging arterial spin labeling hypoperfusion with diffusion-weighted image hyperintensity is useful for diagnostic imaging of Creutzfeldt–Jakob disease - Kitazaki, Yuki; Ikawa, Masamichi; Hamano, Tadanori; Sasaki, Hirohito; Yamaguchi, Tomohisa; Enomoto, Soichi; Shirafuji, Norimichi; Hayashi, Kouji; Yamamura, Osamu; Tsujikawa, Tetsuya; Okazawa, Hidehiko; Kimura, Hirohiko; et al. (Frontiers in Neurology, 2023)
Background and Objectives: Magnetic resonance imaging with arterial spin labeling (ASL) perfusion imaging is a noninvasive method for quantifying cerebral blood flow (CBF). We aimed to evaluate the clinical utility of ASL perfusion imaging to aid in the diagnosis of Creutzfeldt-Jakob disease (CJD). Methods: This retrospective study enrolled 10 clinically diagnosed with probable sporadic CJD (sCJD) based on the National CJD Research & Surveillance Unit and EuroCJD criteria and 18 healthy controls (HCs). Diffusion-weighted images (DWIs), CBF images obtained from ASL, N-isopropyl-( 123 I)-p-iodoamphetamine ( 123 IMP)-single-photon emission computed tomography (SPECT) images, and 18 F-fluorodeoxyglucose ( 18 FDG)-positron emission tomography (PET) images were analyzed. First, the cortical values obtained using volume-ofinterest (VOI) analysis were normalized using the global mean in each modality. The cortical regions were classified into DWI-High (≥ +1 SD) and DWI-Normal (< +1 SD) regions according to the DWI-intensity values. The normalized cortical values were compared between the two regions for each modality. Second, each modality value was defined as ASL hypoperfusion (< -1 SD), SPECT hypoperfusion (< -1 SD), and PET low accumulation (< -1 SD). The overall agreement rate of DWIs with ASL-CBF, SPECT, and PET was calculated. Third, regression analyses between the normalized ASL-CBF values and normalized SPECT or PET values derived from the VOIs were performed using a scatter plot.The mean values of ASL-CBF (N = 10), 123 IMP-SPECT (N = 8), and 18 FDG-PET (N = 3) in DWI-High regions were significantly lower than those in the DWI-Normal regions (p < 0.001 for all); however, HCs (N = 18) showed no significant differences in ASL-CBF between the two regions. The overall agreement rate of DWI (high or normal) with ASL-CBF (hypoperfusion or normal) (81.8%) was similar to that of SPECT (85.2%) and PET (78.5%) in CJD. The regression analysis showed that the normalized ASL-CBF values significantly correlated with the normalized SPECT (r = 0.44, p < 0.001) and PET values (r = 0.46, p < 0.001) in CJD. Discussion: Patients with CJD showed ASL hypoperfusion in lesions with DWI hyperintensity, suggesting that ASL-CBF could be beneficial for the diagnostic aid of CJD.